2021
DOI: 10.2147/prbm.s294547
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bicultural Identity Integration and National Identity on COVID-19-Related Anxiety Among Ethnic Minority College Students: The Mediation Role of Power Values

Abstract: Purpose The current study investigated the association between bicultural identity integration (BII, incorporating BII-harmony and BII-blendedness), national identity, and anxiety related to Coronavirus disease 2019 (COVID-19) among ethnic minority college students. In addition, this research examined the mediation role of power values in the relationship between BII, national identity, and COVID-19-related anxiety. Methods This cross-sectional research design made use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…The distinct characteristics of each ethnic group, coupled with the huge differences in economic and social development levels, lead to poor educational learning and socio-cultural integration of ethnic minority students. Therefore, the policy should promote integration of academic knowledge, ethnic cultural knowledge, and social emotional support in all aspects, like campus and community activities and family education, instead of just in classrooms (Long et al, 2021). It is necessary to leverage the collaborative role of teachers and curriculum design, to apply into producing what is learned, and to integrate science research and education with industry.…”
Section: Discussionmentioning
confidence: 99%
“…The distinct characteristics of each ethnic group, coupled with the huge differences in economic and social development levels, lead to poor educational learning and socio-cultural integration of ethnic minority students. Therefore, the policy should promote integration of academic knowledge, ethnic cultural knowledge, and social emotional support in all aspects, like campus and community activities and family education, instead of just in classrooms (Long et al, 2021). It is necessary to leverage the collaborative role of teachers and curriculum design, to apply into producing what is learned, and to integrate science research and education with industry.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study performed in 67 countries showed that stronger national identification was linked to higher psychological well-being, but its effect on reducing COVID-19-related threat was negligible (Bonetto et al, 2021). A study of 18 ethnic minorities in China found that stronger identification with their nation (China) and higher bicultural identity integration were related to reduced COVID-19 anxiety (Long et al, 2021).…”
Section: The “Social Cure” Among Minority and Immigrant Groupsmentioning
confidence: 99%
“…For example, some cultures may ascribe the onset of mental illness to possession by evil spirits and black magic, while others promote healing temples and other shrines for people who experience mental illness (Gopalkrishnan, 2018 ). Some Chinese migrants may view mental health issues as a manifestation of a lack of balance in one’s mental and spiritual well-being, such that healing often incorporates spiritual and religious traditions involving acupuncture and herbs, whereas others may perceive mild mental illness as personal problems to be addressed by an elder in the family or a spiritual leader (Kramer et al, 2002 ; Long et al, 2021 ). Varying conceptualizations of mental illness across cultures often stem from differences in collectivism (Altweck et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%